Muslce activation patterens in XC-skiers suffering from CACS - Bakker, E.; Federolf, P. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
A large proportion of elite cross-country (XC) skiers suffer from chronic anterior compartment syndrome (CACS), however, it remains largely unknown what factors may trigger or aggravate this condition (Lawson et al., 1992). Therefore it is important to identify physiological changes that accompany CACS symptoms. The purpose of this study was to investigate differences in the muscle activation patterns between XC skiers suffering from CACS symptoms and a healthy control group. It was hypothesized that (H1) when increasing skate effort, skiers in the CACS group show disproportionate increases in the EMG intensity of affected muscles and (H2) the frequency distribution in the EMG power spectrum of affected muscles shifts to lower frequencies.